2020
DOI: 10.1016/j.mehy.2020.110229
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of endothelial dysfunction: A novel method to predict severe COVID-19?

Abstract: The COVID-19 pandemic caused by the SARS-CoV-2 virus has infected millions and overburdened the healthcare infrastructure globally. Recent studies show that the endothelial dysfunction caused by the virus contributes to its high morbidity and mortality. A parameter that can identify patients who will develop complications early will be valuable in patient management and reducing the burden on medical resources. An emerging technology is currently being tested to predict the cardiovascular risk via non-invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Regarding the first assumption, it should be emphasized that bFMD measurement is a non-invasive and easy bedside procedure that provides a result in real time [45]. Therefore, the measurement of bFMD in COVID-19 patients at hospital admission might refine our prognostic ability and possibly improve decision-making about medical care intensity [14]. In this regard, as several drugs against severe COVID-19 are currently under investigation and being tested in clinical trials, the measurement of bFMD upon hospital admission may provide an option to select patients who might benefit from a more intensive treatment approach based on experimental drugs beyond the standard of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first assumption, it should be emphasized that bFMD measurement is a non-invasive and easy bedside procedure that provides a result in real time [45]. Therefore, the measurement of bFMD in COVID-19 patients at hospital admission might refine our prognostic ability and possibly improve decision-making about medical care intensity [14]. In this regard, as several drugs against severe COVID-19 are currently under investigation and being tested in clinical trials, the measurement of bFMD upon hospital admission may provide an option to select patients who might benefit from a more intensive treatment approach based on experimental drugs beyond the standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of these lines of evidence, great interest has arisen in the search for markers of endothelial injury with potential clinical utility for the stratification of COVID-19 prognosis [12,14]. To date, several cross-sectional, retrospective, and prospective studies have reported significant discriminatory value of some laboratory markers of endothelial dysfunction and damage (e.g., circulating endothelial cells, soluble Intercellular Adhesion Molecule 1, and von Willebrand Factor Antigen) toward COVID-19 severity and clinical outcomes [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction is characterized by a modification of the balance between vasodilator, anti-mitotic, anti-thrombogenic and anti-adhesive substances, in favor of those known as vasoconstrictors, pro thrombogenes, pro adhesives and proliferatives [7] [8] [9] [19]. Despite the controversies regarding their lower sensitivity compared to non-invasive methods [19] [25] [30] [33] [34] [36]- [42], the choice of ET-1 and VCAM-1 as markers of endothelial dysfunction is due to makes their sensitivities and specificities identical to those of other biomarkers of ED [19]- [25] [30] [33] [34] [36] [40] [41] [42]. Regarding the fact that their dosage is not carried out routinely and therefore without reference values, the recruitment of people free from any pathology made it possible to obtain a control value for these two markers.…”
Section: The Choice Of Markers For Endothelial Dysfunctionmentioning
confidence: 99%
“…Yoganandamoorthy u. Mitarb. [61] plädieren für ebenfalls nicht invasive Messmethoden der vaskulären Funktion bei COVID-19-Patienten, wie dem Verlust der dikroten Welle in der Druckpulskurve oder einem geringeren Temperaturanstieg im Rahmen einer reaktiven Hyperämie nach suprasystolischer Okklusion der Armarterien [61].…”
Section: Sars-cov-2-induzierte Endotheliitisunclassified